2021
DOI: 10.3389/fmats.2021.750247
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Zn (II)-Based Nanoprobes: A Highly Symmetric Supramolecular Platform for Sensing of Biological Targets and Living Cell Imaging

Abstract: Zinc (II) cation is an environmentally friendly metal, less expensive, easy to dispose of, and managed. Highly engineered symmetric systems can be built using zinc (II) atoms as the metal nodes of hybrid organic-inorganic supramolecular structures. In biological contexts, luminescent zinc-based nanoprobes are in growing demand. Specifically, they are currently employed to detect biologically and environmentally relevant analytes, in therapeutic drug delivery, and for bioimaging and diagnostic techniques monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 154 publications
0
2
0
Order By: Relevance
“…It was also observed by the authors that ZIF-8 exerted characteristics for topical skin use with low radical production, low skin penetration, low toxicity, high transparency, and high stability. On the basis of obtained results they concluded that ZIF-8 could potentially be a safe and effective sunscreen surrogate for human, and MOFs could be a novel source to develop more effective and safe UV filters A team of Rosita Diana, Lucia Sessa, Simona Concilio, Stefano Piotto and Barbara Panunzi [59], were also reported luminescent Zn (II)-based nanoprobe, which is a highly symmetric supramolecular platform for sensing of biological targets and living cell imaging. Cheng, Jiapeng et al [60], reported the synthesis of stable zinc-MOF materials by using fluorenone carboxylate ligand and expressed multifunctional detection and photocatalysis degradation property.…”
Section: Synthesis and Applicationmentioning
confidence: 99%
“…It was also observed by the authors that ZIF-8 exerted characteristics for topical skin use with low radical production, low skin penetration, low toxicity, high transparency, and high stability. On the basis of obtained results they concluded that ZIF-8 could potentially be a safe and effective sunscreen surrogate for human, and MOFs could be a novel source to develop more effective and safe UV filters A team of Rosita Diana, Lucia Sessa, Simona Concilio, Stefano Piotto and Barbara Panunzi [59], were also reported luminescent Zn (II)-based nanoprobe, which is a highly symmetric supramolecular platform for sensing of biological targets and living cell imaging. Cheng, Jiapeng et al [60], reported the synthesis of stable zinc-MOF materials by using fluorenone carboxylate ligand and expressed multifunctional detection and photocatalysis degradation property.…”
Section: Synthesis and Applicationmentioning
confidence: 99%
“…Optical probes offer in situ observation, real-time and fast-response monitoring, sensitivity, selectivity [ 1 , 2 , 3 ], and even by the non-invasive approach required for living tissues [ 4 , 5 , 6 ]. Colorimetric/fluorescent tools revolutionized the ability to probe biological dynamics at the cellular level on several platforms: small-molecule dyes, metal complexes, and fluorescent proteins [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%